Design and development of an autonomous sumo robot - Saw, Han Beng. (2010)
The aim of this project is to design and develop an autonomous sumo robot for the purpose of fulfilling an educational experience and to compete in the Singapore Robotic Games 2010. An autonomous sumo robot is able to have a match with another sumo robot without continuous human guidance. It is expected to deploy offensive or defensive movements in response to movements from the opponent with an ultimate intention to win via pushing opponent out of the ring.